Musa Jarullah Bigiyev - Akhmetova, Elmira (2015)
Musa Jārullāh Bigiyev was a Muslim Tatar religious scholar, journalist, politician, educator and a prolific writer, who devoted his entire life to reconciling Islam with modern progress. He published more than sixty books in Arabic and Old Ottoman dealing with the issues of Islamic jurisprudence, theology, sciences of the Qur’an, sciences of the hadith, literature, economics, law, politics and history.